Solid-state ¹?F-NMR studies on fluorine-labeled model compounds and biomolecules - Dürr, Ulrich Heiner Nikolaus (KIT Scientific Publishing, 2006)
The fluorine nucleus, when introduced as a reporter group in membrane-associated proteins or peptides, offers a highly sensitive alternative to conventional isotope labels in solid-state NMR spectroscopy. The study presented here is concerned with the development of 19F-NMR methods, as well as data analysis schemes to extract the wealth of structural and motional information from the spectra.